The Heterogeneity of Empathy: Possible Treatment for Anhedonia? - Light, Sharee N. (Frontiers in Psychiatry, 2019)
Traditionally, empathy has been described as a process by which an individual “tries on” the negative emotion of others (i.e. empathic concern). A corpus of empirical work has been devoted to the study of this particular form of empathy. However, in this paper, the heterogeneity model of empathy is proposed as a method for counteracting the lack of attention paid to “positive-valence empathy”— our ability to respond to the negative and positive emotion of others with appropriate positive affect. Both empathic concern and positive-valence empathy are argued to have distinguishable behavioral manifestations and at least partially distinguishable neurobiological underpinnings. The potential value of positive-valence empathy induction for therapeutic purpose is also discussed.